Thermal Instability of Commercial Dual-axis MEMS Accelerometers - Łuczak, Sergiusz; Zams, Maciej; Pieńczuk, Paweł (Micro and Nanosystems, 2023)
Introduction: Thermal drifts of MEMS sensors are one of their biggest shortcomings. However, experimental studies may offer a solution while striving for the reduction of related errors.Objective: The aim was to determine the thermal drifts of MEMS accelerometers associated with the offset voltage and the scale factor and then to propose a way of reducing the resultant errors.Methods: Four commercial dual-axis MEMS accelerometers (two pieces of ADXL 202E and two pieces of ADXL 203 by Analog Devices Inc.) with analog outputs were experimentally tested with respect to their thermal instability, employing two computer-controlled test rigs that provided a stable orientation of the accelerometers.Results: It was found that the thermal drifts of the offset voltage generated by the tested accelerometers were considerable, resulting in respective errors of about 14 mg (ADXL 202E) or 7 mg (ADXL 203), whereas catalog values of drifts of the scale factor were much lower.Conclusion: The determined values are smaller than their counterparts specified in the relevant manufacturer datasheets; significant differences exist between the tested pieces of the two accelerometers (40% or 78%) as well as between the two sensitive axes of a single accelerometer (84% or 80%), this can be taken into consideration while striving for a higher accuracy of an acceleration measurement.
Keywords: error